The costs and returns associated with corn-, milo-, and wheat-based swine diets - Michael R Langemeier (Kansas Agricultural Experiment Station Research Reports, 1990)
Feed costs per hundred weight for farrow-to-finish operations in Kansas were generally lower for a milo-based diet than for corn-based or wheat-based diets. Use of corn and wheat in the diet was economical for short periods of time only. Feed costs were found to be consistently higher and returns per head consistently lower when com and wheat were fed over the entire farrowing to market period.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Grain; Economics; Marketing